IMPLEMENTASI PEMBIASAAN BERKATA ‘TOLONG’, ‘MAAF’, ‘TERIMA KASIH’, DAN ‘PERMISI’ DALAM PEMBENTUKAN KARAKTER ANAK USIA 5-6 TAHUN DI KOBER SARTIKA ASIH - Nurhayati, Ida; Hidayat, Yusuf; Lastari, Lastari; Kurniasih, Neng; Susanti, Susi (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2024)
As an effort to generate the quality generation, from the early age character education must have been familiarized through a series of habituation. The present study aims to determine the implementation of habituation method of saying please, sorry, thank you, and excuse me for character building in early childhood. This research uses qualitative method under a descriptive approach. The results showed that the implementation of habituation to say four magic words, namely: the word 'sorry', 'thank you', 'please', and 'excuse me' in early childhoods aged 5-6 years is generally exemplified through modelling showed by teacher and familiarized through direct practice. In addition, the implementation of the habituation of the four magic words is carried out in several steps including: the teacher as the role model provides stimulus to early childhoods by training them to speak to teacher and friends politely, the teacher invites early childhoods to have habituation in saying the four magic words through active communication, the teacher instills habituation learning of four magic words through songs, the teacher provides understanding of the four magic words by modeling directly to early childhoods. The positive impacts obtained by early childhoods include: they are accustomed to say the word ‘please’ before asking for a help, they are accustomed to say the word ‘sorry’ to other friends when making mistakes, they are accustomed to say the word ‘thank you’ when given something by friends, they are accustomed to say the word ‘excuse me’ when will pass in front of others. In conclusion, the implementation of habituation to say four magic words in early childhoods aged 5-6 years is directly exemplified through teacher’s modelling and habituation.